1977
DOI: 10.1002/er.4440010403
|View full text |Cite
|
Sign up to set email alerts
|

Ventilation: A behavioural approach

Abstract: Behavioural studies of the window‐opening habits of families in one hundred and twenty three houses show a strong seasonal pattern. During winter window opening is closely related to moisture level in the external air. In summer it is more closely linked to mean daily temperature. There are wide differences between families, with larger families having more open windows. Re‐examination of ventilation criteria suggests three seasons, one in deep winter which needs minimum adequate air for body odour removal, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 1 publication
1
20
0
Order By: Relevance
“…Many studies have investigated the behaviour of people in residential buildings [3][4][5][6][7][8][9]. The studies have resulted in defining patterns of human behaviour in relation to window opening, use of airconditioning and control of temperature, lighting and solar shading, depending on outdoor and indoor conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have investigated the behaviour of people in residential buildings [3][4][5][6][7][8][9]. The studies have resulted in defining patterns of human behaviour in relation to window opening, use of airconditioning and control of temperature, lighting and solar shading, depending on outdoor and indoor conditions.…”
Section: Introductionmentioning
confidence: 99%
“…When the cross-sectional questionnaire survey data could be complemented with additional datasets, such as environmental measurements, more sophisticated statistical methods could be used to find a connection between variables. This connection was described through correlation in many studies (Brundrett 1977) (Iwashita and Akasaka 1997) (Moore et al 2003) (Lutzenhiser 1992) (Price and Sherman 2006) (Guerra-Santin and Itard 2010) (Becker and Paciuk 2009) (Hua et al 2011). Others also managed to build a regression model to describe the nature of the connection (Frontczak et al 2012) (Humphreys 2005) (Raja et al 2001) (Meier and Rehdanz 2010) (Sardianou 2008) (Rijal 2008) (Bekö et al 2011) (Brager et al 2004) (Warren and Parkins 1984) (Rijal et al 2007).…”
Section: Data Analysis Methodsmentioning
confidence: 99%
“…An early study (Brundrett 1977) focused on window opening drivers during three seasons. Brundrett found that opening windows during winter strongly correlates to outdoor air moisture levels, while during the summer the mean daily temperature is a more important driver.…”
Section: Opening Windowsmentioning
confidence: 99%
“…Questionnaire surveys are often used to identify the most important factors affecting occupant interactions with building control systems including: window opening behavior [23,24,26,55,73,[76][77][78]88], the use of heating [26,33,83,85,89] and cooling [37,84,87], solar shading and blinds [20,26,29,65], electrical lighting [26,31,81] and equipment [52,86]. The surveys are typically carried out by sending out invitations to a consistent amount of building occupants which are representative of the building population.…”
Section: Questionnaires and Self-reportingmentioning
confidence: 99%
“…Questionnaires [23,55,73,77,78,80,88] Mail survey [99] Web based survey [88,107] Questionnaires [29,30,50,65,73,78] Questionnaires [31,81] Questionnaires [82][83][84][85]89] Questionnaires [52,86,87] …”
Section: Interview Techniquesmentioning
confidence: 99%